(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
The mediation between the favela and the fashion catwalks of the south zone of Rio, proposed by Jacaré Modas - a modeling agency created in the Jacarezinho’s favela - which is shown in the documentary Favela é Moda, incites an agency of concepts and ideas coming from different perspectives, to think about the favela-walkway path through its biopower aspect. The Molecular Revolutions and War Machines of Guattari and Deleuze, the theory of Amerindian Perspectivism oferte by Eduardo Viveiros de Castro and its unfolding in the idea of Communication through Equivocation, suggested by Evandro Medeiros and Lara Linhalis, support a reading on this phenomenon of displacement of peripheral bodies to places not foreseen for them.